Contrastive and Error Analyses in Inverted Order to Facilitate English Language Teaching - Saini, Shivani (Beyond Words, 2016)
Both Contrastive and Error Analysis have vital roles in accounting for problems in teaching English as a foreign/second language (TEFL/TESL). Contrastive Analysis (CA) compares languages and makes predictions about possible errors learners make due to the influence of their first language (L1), while Error Analysis (EA) analyses pupilsâ€™ compositions or conversations and investigates different sources of errors one of which is cross linguistic influence. It is obvious that CA and EA are not the same. They overlap in a certain area, but they are not competing against each other. Both CA and EA can be used in a complementary role in understanding learnersâ€™ errors in second language learning. In the present article, a teaching methodology (â€œa contrastive approachâ€ to EA) will be explored where the traditional order of conducting CA and EA (where CA leads to EA) has been inverted. The approach in the present study is that the job of diagnosis belongs to EA and here CA can be used as complementary to EA as a remedial procedure